2018
DOI: 10.1177/0047287518764345
|View full text |Cite
|
Sign up to set email alerts
|

Flying to Quality: Cultural Influences on Online Reviews

Abstract: Customers increasingly consult opinions expressed online before making their final decisions. However, inherent factors such as culture may moderate the criteria and the weights individuals use to form their expectations and evaluations. Therefore, not all opinions expressed online match customers' personal preferences, neither can firms use this information to deduce general conclusions. Our study explores this issue in the context of airline services using Hofstede's framework as a theoretical anchor. We gau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 78 publications
2
58
0
2
Order By: Relevance
“…Extant studies in this stream explore, among others, consumer motivation to participate on eWOM (Tong, Wang, Tan, & Teo, 2013), review characteristics that affect the credibility of eWOM (Luo, Luo, Xu, Warkentin, & Sia, 2015) or their helpfulness (Korfiatis, García-Barriocanal, & Sánchez-Alonso, 2012;Krishnamoorthy, 2015;Ngo-Ye, Sinha, & Sen, 2017). However, the pertinent question on how firms can utilize the information content of online reviews is focused on either extracting information that reflects customer preferences in order to improve their products (Law, Gruss, & Abrahams, 2017;Zhang, Xu, & Wan, 2012) or understand the demographic or cultural characteristics of their clients (Stamolampros, Korfiatis, Kourouthanassis, & Symitsi, 2018).…”
Section: Background and Related Work 21 Information Content Of Onlinmentioning
confidence: 99%
“…Extant studies in this stream explore, among others, consumer motivation to participate on eWOM (Tong, Wang, Tan, & Teo, 2013), review characteristics that affect the credibility of eWOM (Luo, Luo, Xu, Warkentin, & Sia, 2015) or their helpfulness (Korfiatis, García-Barriocanal, & Sánchez-Alonso, 2012;Krishnamoorthy, 2015;Ngo-Ye, Sinha, & Sen, 2017). However, the pertinent question on how firms can utilize the information content of online reviews is focused on either extracting information that reflects customer preferences in order to improve their products (Law, Gruss, & Abrahams, 2017;Zhang, Xu, & Wan, 2012) or understand the demographic or cultural characteristics of their clients (Stamolampros, Korfiatis, Kourouthanassis, & Symitsi, 2018).…”
Section: Background and Related Work 21 Information Content Of Onlinmentioning
confidence: 99%
“…To counter this weakness, online reviews have been recognized as a recent data source worthwhile to exploit. Various studies using reviews have demonstrated their value and usefulness in related research [14,17,25,26,41,45,52]. Online reviews are easily gathered with big data in real-time [22].…”
Section: Survey-based Versus Data Analytics-based Service Evaluationmentioning
confidence: 99%
“…The discovery of airport passenger satisfaction is crucial information for airport managers. Stamolampros, Korfiatis, Kourouthanassis, and Symitsi [26] explored the cultural influences implied in online reviews and ratings through topic modeling. According to the results of their study, customers were more likely to be satisfied because providers recognized the specific level of cultural influences.…”
Section: Survey-based Versus Data Analytics-based Service Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of quantitative research, online customer ratings have been used preferentially on the specialized websites of TripAdvisor, Booking, and HolidayCheck [25,[38][39][40][41]. However, in the airline sector, research has been limited, especially in the statistical analysis of the scales and competitive positioning studies [42][43][44].…”
Section: Introductionmentioning
confidence: 99%